Inhomogeneous quantum group of Q-fermions - Ozkan, Erdogan Mehmet; Ozavsar, Muttalip (YILDIZ TECHNICAL UNIV, 2023)
In this work, we introduce a nonstandard algebra of q-fermions where q is a nonzero complex deformation parameter for the algebra of the commuting fermions. In order to show that q-fermions provides a proper generalization of the algebra of usual commuting fermions, we prove that there is an inhomogeneous quantum structure associated with q-fermions for a complex number q with |q| = 1.
Keywords: Quantum Invariance Group; Fermions; Hopf Algebra; Inhomogeneous Quantum Group; Q-ANALOG; OSCILLATOR; Engineering